THE INFLUENCE OF PRODUCT VARIATION AND SERVICESCAPE ON CUSTOMER SATISFACTION AT KOPI KENANGAN MEGAMAS MANADO - Glady Langi; Maryam Mangantar; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The objectives to be achieved in this study are to identify the influence of product variations on customer satisfaction at Kopi Kenangan Megamas Manado, identify the influence of servicescape on customer satisfaction at Kopi Kenangan Megamas Manado, the influence of product variations and servicescape on customer satisfaction at Kopi Kenangan Megamas Manado. This study uses a quantitative approach. The sampling method used was non-probability with a purposive sampling technique. The sample criteria for this study were people who had visited, purchased and dine in at Kopi Kenangan Kawasan Megamas Manado. The results show that Product Variation has a positive and significant influence on Customer Satisfaction at Kopi Kenangan Megamas Manado, Servicescape has a positive and significant influence on Customer Satisfaction at Kopi Kenangan Megamas Manado, and simultaneously Product Variation and Servicescape influence Customer Satisfaction   Keyword: product variation, servicescape, customer satisfaction